Automatic Off-Line Design of Robot Swarms: A Manifesto - Birattari, Mauro; Ligot, Antoine; Bozhinoski, Darko; Brambilla, Manuele; Francesca, Gianpiero; Garattoni, Lorenzo; Garzón Ramos, David; Hasselmann, Ken; Kegeleirs, Miquel; Kuckling, Jonas; Pagnozzi, Federico; Roli, Andrea; et al. (Frontiers in Robotics and AI, 2019)
Designing collective behaviors for robot swarms is a difficult endeavor due to their fully distributed, highly redundant, and ever-changing nature. To overcome the challenge, a few approaches have been proposed, which can be classified as manual, semi-automatic, or automatic design. This paper is intended to be the manifesto of the automatic off-line design for robot swarms. We define the off-line design problem and illustrate it via a possible practical realization, highlight the core research questions, raise a number of issues regarding the existing literature that is relevant to the automatic off-line design, and provide guidelines that we deem necessary for a healthy development of the domain and for ensuring its relevance to potential real-world applications.